Approach of the concept chemical transformation in the 4th elementary school year focusing on a textbook (Revista Contexto & Educação, 2025)
The textbook (LD) perform an important role in the teaching and learning process, being relevant to understand its specifications in the Elementary School prime years, in which professors have a lack of especific graduation in grounds, such as natural science (CN). The article analyse the approaching concept “chemical transformation” on a natural science textbook used in the 4th elementary school year. The building process and data analisys, inspired by assumptions on textual discourse analysis (Moraes; Galiazzi, 2016), flags the importance of daily relationship, allowing to create two categorys: concept approach “chemical transformation” with and without the usage of the word “substance”. The results endorse the LD contribuition to the access of scholar knowledge implied in the relationship between the daily relationship and science, through dynamic process of conceitual signification with student's systematical engagement in the scholarship studies, being able to stimulate the critical thinking founded through scientifical knowledge, in favor of a better world.
Keywords: Natural Science; Concept Formation; Textbook; Elementary School